Intradevice and Interdevice Agreement Between a Rebound Tonometer, Icare PRO, and the Tonopen XL and Kowa Hand-held Applanation Tonometer When Used in the Sitting and Supine Position. Issue 7 (September 2015) - Nakakura, Shunsuke; Mori, Etsuko; Yamamoto, Minami; Tsushima, Yuuri; Tabuchi, Hitoshi; Kiuchi, Yoshiaki
<x xml:space="preserve">Abstract</x> Purpose: The aim of the study was to investigate the agreement between a new portable tonometer, Icare PRO, and the Tonopen XL and Kowa hand-held applanation tonometers (HAT). Methods: The right eyes of 127 healthy subjects were enrolled. Intraocular pressure (IOP) was measured in both sitting and supine positions using the Icare PRO, Tonopen XL, and Kowa HAT tonometers. The repeatability of the IOP measurements was evaluated by calculating intraclass correlation coefficients. Between-method agreements of tonometer measurements were evaluated using Bland-Altman analysis. Results: Intradevice agreement: The intraclass correlation coefficients (sitting, supine) of Icare PRO, Tonopen XL, and Kowa HAT were (0.863, 0.656), (0.845, 0.819), and (0.957, 0.956), respectively. Interdevice agreement: The Bland-Altman analysis revealed that, in the sitting position, the mean differences between Icare PRO and Tonopen XL, and between Icare PRO and Kowa HAT were −0.43 and 0.43 mm Hg, respectively (95% limits of agreement: −6.24 to 5.34 mm Hg, −4.04 to 4.90 mm Hg). In the supine position, the corresponding mean differences were −0.88 and 0.14 mm Hg (95% limits of agreement: −5.66 to 3.91 mm Hg, −4.06 to 4.33 mm Hg). IOP differences between Icare PRO and the other tonometers were unaffected by central corneal thickness. Conclusions: The repeatability of Icare PRO was slightly lower in the supine position than in the sitting position. Although Icare PRO underestimated IOP values in eyes with higher IOP when compared with Tonopen XL and Kowa HAT in both positions, we observed good interdevice agreement between Icare PRO and both Tonopen XL and Kowa HAT.